Systemic experiential learning model for the evaluation of technological learning: the case of small satellite capability-building in Algeria - Ayad, Ahmed; Wilkinson, Edith; Matthews, Ron (Intellect, 2019)
This article proposes a ‘systemic experiential learning model’ for the evaluation of technological learning. Technological learning is effective when combining learning by doing, by searching and by interacting. The proposed model is based on parallels drawn between the typology – learning by doing, by searching and by interacting – and Kolb’s Experiential Learning Theory through its cyclical combination of action and reflection. It argues that learners, whether they be individuals, groups, organizations or inter-organizations, are more effective when completing Kolb-like cycles. The proposed model is the combination of horizontal and vertical processes. Each learning level (individual, group, organization or inter-organization) is modelled, horizontally, according to a Kolb-like learning cycle. Vertical connections are made between the horizontal levels of aggregation by borrowing March’s concepts of exploration and exploitation. The model has been used for the evaluation of learning occurring in the Algerian small satellite capability-building programme. The implementation of the model revealed that learning is not systemic and therefore ineffective. Findings are reflective of the difficulty of striking the right balance between action (learning by doing) and reflection (learning by searching) and densifying interactions (learning by interacting) within and between learning levels.
Keywords: Technological learning; experiential learning; knowledge diffusion; technological capability-building; small satellite